2007
DOI: 10.1103/physrevlett.98.193201
|View full text |Cite
|
Sign up to set email alerts
|

(e,3e)on Helium at Low Impact Energy: The Strongly Correlated Three-Electron Continuum

Abstract: Double ionization of the helium atom by slow electron impact (E(0)=106 eV) is studied in a kinematically complete experiment. Because of a low excess energy E(exc)=27 eV above the double ionization threshold, a strongly correlated three-electron continuum is realized. This is demonstrated by measuring and calculating the fully differential cross sections for equal energy sharing of the final-state electrons. While the electron emission is dominated by a strong Coulomb repulsion, also signatures of more complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 27 publications
3
48
1
Order By: Relevance
“…Much less is known about correlated dynamics in four-body Coulomb systems, more precisely on differential observables for fragmentation of a three-electron atom in its nucleus and all electrons [5][6][7][8]. A recent experiment provides for the first time detailed information in terms of differential cross sections on the angular and energetic breakup parameters of three electrons following impact double ionization of Helium [9]. For small excess energies E (each continuum electron carries away about 9 eV energy), it was found that the electrons form an equilateral triangle upon breaking away from the nucleus.…”
mentioning
confidence: 99%
“…Much less is known about correlated dynamics in four-body Coulomb systems, more precisely on differential observables for fragmentation of a three-electron atom in its nucleus and all electrons [5][6][7][8]. A recent experiment provides for the first time detailed information in terms of differential cross sections on the angular and energetic breakup parameters of three electrons following impact double ionization of Helium [9]. For small excess energies E (each continuum electron carries away about 9 eV energy), it was found that the electrons form an equilateral triangle upon breaking away from the nucleus.…”
mentioning
confidence: 99%
“…Recent advances in measurement techniques have allowed kinematically complete measurements of the electron-impact double ionization of helium to be made [1,2]. Together with fully differential measurements for the electron-impact single ionization with excitation [3] (where the He + ion is left in an excited state), a significant insight has been given into the complex dynamics of the full four-body system.…”
Section: Introductionmentioning
confidence: 99%
“…While theoretical methods have provided accurate ab initio calculations for the three-body channels open to these collisions, such as convergent close coupling (CCC) [4], R matrix with pseudostates (RMPS) [5], and time-dependent close coupling (TDCC) [6], the progress of ab initio methods on the four-body channels has been limited. Hybrid methods that combine CCC or RMPS with distorted-wave techniques, or indeed full distorted-wave methods, have made some progress in this regard [1,3] though large discrepancies remain, especially with low-energy collisions. Presently, TDCC is the only ab initio method that has been applied to electron-impact double ionization of helium, and while it is in reasonable agreement with measurements of the total cross sections [7], angular-differential calculations differ markedly from measurement [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many four-body processes such as double excitation and ionization with excitation are yet to be explored with this method, so the electron-helium system remains only partially solved. Given the kinematically complete "reaction microscope" measurements [9,10] for helium that have been performed recently, the demand for accurate theoretical modeling of four-body processes is increasing.…”
Section: Introductionmentioning
confidence: 99%